Erratum: RIVERA, JULIO (2010) Lost and found: Rediscovery of the genus Margaromantis Piza, 1982 and consequential nomenclatural changes in the genus Colombiella Koçak & Kemal, 2008 (Mantodea: Mantidae, Photinainae). Zootaxa, 2529, 65–68. - Rivera, Julio (Zootaxa, 2010)
(Erratum)